Depressive symptoms among people under COVID-19 quarantine or self-isolation in Korea: a propensity score matching analysis - Chu, Hyeon Sik; Lee, Kounseok (Frontiers in Psychiatry, 2023)
Introduction: This study aims to determine the effect of COVID-19-related hospital isolation or self-isolation on depression using the propensity score matching method.Methods: Data on 217,734 participants were divided into groups based on whether or not they underwent quarantine for their COVID-19 diagnosis. COVID-19-related anxiety, depressive symptoms, subjective health status, and perceived stress were evaluated.Results: Based on the calculated propensity score, we matched the quarantined group and nonquarantined group using 1:2 matching with nearest neighbor matching and a caliper width of 0.1. Within the quarantined group, 16.4% of participants experienced significant depressive symptoms, which was significantly higher than that of the non-quarantined group. However, there was no significant difference between the two groups in COVID-19-related anxiety, self-rated health status, and perceived stress. In our multiple logistic regression analysis with related variables corrected, the quarantined group was 1.298 times more likely to have depressive symptoms than the nonquarantined group (95% CI=1.030-1.634).Our study confirmed that COVID-19 quarantine is associated with depressive symptoms. These results indicate that healthcare policymakers and healthcare professionals must consider the negative mental and physical effects of quarantine when determining quarantine measures during an infectious disease disaster such as the COVID-19 pandemic.